2012
DOI: 10.1373/clinchem.2011.169318
|View full text |Cite
|
Sign up to set email alerts
|

Nonhematopoietically Derived DNA Is Shorter than Hematopoietically Derived DNA in Plasma: A Transplantation Model

Abstract: BACKGROUND Plasma DNA is predominantly hematopoietic in origin. The size difference between maternal- and fetal-derived DNA in maternal plasma prompted us to investigate whether there was any discrepancy in molecular size between hematopoietically and nonhematopoietically derived DNA in plasma. METHODS Plasma DNA samples from 6 hematopoietic stem cell transplant recipients and 1 liver transplant recipient were analyzed by mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
92
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(105 citation statements)
references
References 28 publications
9
92
0
Order By: Relevance
“…3 in the online Data Supplement). These data are consistent with our previous findings that hematopoietic cells are the predominant source of DNA in human plasma (23 ).…”
Section: Plasma Methylomessupporting
confidence: 93%
See 1 more Smart Citation
“…3 in the online Data Supplement). These data are consistent with our previous findings that hematopoietic cells are the predominant source of DNA in human plasma (23 ).…”
Section: Plasma Methylomessupporting
confidence: 93%
“…We used paired-end sequencing to determine the lengths of plasma DNA molecules (23,32 ). In a previous study, we showed that plasma DNA molecules had sizes that approximated those of mononucleosomes and that fetal DNA molecules were shorter than maternal ones (32 ).…”
Section: Relationship Between Methylation Status and The Size Of Dna mentioning
confidence: 99%
“…Different mechanisms accounting for DNA release in the circulation have been postulated, including apoptosis (23)(24)(25)(26), necrosis (26), and active secretion (27)(28)(29). Observations in gender-mismatched bone marrow and solid organ transplantation models point to hematopoietic cells as primary source of cfDNA in the plasma, with nonhematopoietic cells accounting for a minority of the free circulating DNA (24,30,31).…”
Section: Introductionmentioning
confidence: 99%
“…Observations in gender-mismatched bone marrow and solid organ transplantation models point to hematopoietic cells as primary source of cfDNA in the plasma, with nonhematopoietic cells accounting for a minority of the free circulating DNA (24,30,31). After crossing the kidney barrier by glomerular filtration, low molecular weight DNA fragments can appear in the urine, called ''transrenal DNA'' (Tr-DNA), whereas higher molecular weight DNA is derived from cells shed from the urinary tract or other urinary cells (32,33) ( Figure 1 and Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…PCR primers were designed to locate within (i.e., internal PCR) and flank the deleted region (i.e., external PCR) of each CND marker in the panel. Short amplicons, ranging in size from 58 to 74 bp (mean 65 bp) were chosen for the internal PCRs so that they would be suitable for quantification of plasma ccfDNA, which is highly fragmented (11 ).…”
Section: Sample Genotypingmentioning
confidence: 99%